Progesterone Receptor Membrane Component 1 (PGRMC1) Expression in Murine Retina. (2nd August 2016) - Shanmugam, Arul K.; Mysona, Barbara A.; Wang, Jing; Zhao, Jing; Tawfik, Amany; Sanders, A.; Markand, Shanu; Zorrilla, Eric; Ganapathy, Vadivel; Bollinger, Kathryn E.; Smith, Sylvia B.
ABSTRACT: Purpose : Sigma receptors 1 (σR1) and 2 (σR2) are thought to be two distinct proteins which share the ability to bind multiple ligands, several of which are common to both receptors. Whether σR1 and σR2 share overlapping biological functions is unknown. Recently, progesterone receptor membrane component 1 (PGRMC1) was shown to contain the putative σR2 binding site. PGRMC1 has not been studied in retina. We hypothesize that biological interactions between σR1 and PGRMC1 will be evidenced by compensatory upregulation of PGRMC1 in σR1 −/− mice. Methods : Immunofluorescence, RT-PCR, and immunoblotting methods were used to analyze expression of PGRMC1 in wild-type mouse retina. Tissues from σR1 −/− mice were used to investigate whether a biological interaction exists between σR1 and PGRMC1. Results : In the eye, PGRMC1 is expressed in corneal epithelium, lens, ciliary body epithelium, and retina. In retina, PGRMC1 is present in Müller cells and retinal pigment epithelium. This expression pattern is similar, but not identical to σR1. PGRMC1 protein levels in neural retina and eye cup from σR1 −/− mice did not differ from wild-type mice. Nonocular tissues, lung, heart, and kidney showed similar Pgrmc1 gene expression in wild-type and σR1 −/− mice. In contrast, liver, brain, and intestine showed increased Pgrmc1 gene expression in σR1 −/− mice. Conclusion : Despite potential biological overlap, deletion of σR1 did not result in a compensatory change in PGRMC1 protein levels in σR1 −/− mouse retina. Increased Pgrmc1 gene expression in organs with high lipid content such as liver, brain, and intestine indicates a possible tissue-specific interaction between σR1 and PGRMC1. The current studies establish the presence of PGRMC1 in retina and lay the foundation for analysis of its biological function.